Burnout and Resilience in the Community-Based Pharmacist Practitioner - Kristine M. Cline; Bella Mehta (University of Minnesota Libraries Publishing, 2022)
Objective: The primary objective was to assess presence of community-based pharmacist practitioner burnout and workplace stress through administration of validated tools. Methods: Pharmacists licensed in Ohio received an invitation to participate in the anonymous online assessment via Qualtrics™ using emails available via the State Board of Pharmacy listserv. The survey assessed emotional exhaustion, depersonalization, and personal accomplishment using a validated tool, the Maslach Burnout Inventory (MBI). The Areas of Worklife Survey (AWS) was used to assess stressors as they relate to burnout and job stress. This study was approved by The Ohio State University Institutional Review Board. Results: There were 1,425 complete responses. Based on the study sample, 67.2% of community-based pharmacists are experiencing burnout. When asked to self-identify workplace stressors, respondents primarily described the Workload, Control, and Reward dimensions of the AWS. The most commonly reported coping mechanisms were self-care strategies (28.4%), mindfulness (17.6%), and personal time/time off (15.3%). Respondents suggested that organizations address staffing (50.2%) and development of a culture of well-being (17.2%) to promote well-being. Conclusion: This study allowed insight into workplace stressors for community-based pharmacists and strategies organizations can employ to improve their well-being. Future studies are needed to assess the efficacy of these interventions.